2014
DOI: 10.1371/journal.pone.0089624
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological and Biochemical Responses of a Medicinal Plant (Salvia miltiorrhiza L.) to Stress Caused by Various Concentrations of NaCl

Abstract: Salvia miltiorrhiza, which is commonly known as Danshen, is a traditional Chinese herbal medicine. To illustrate its physiological and biochemical responses to salt stress and to evaluate the feasibility of cultivating this plant in saline coastal soils, a factorial experiment under hydroponic conditions was arranged on the basis of a completely randomised design with three replications. Five salinity treatments (0, 25, 50, 75 and 100 mM NaCl) were employed in this experiment. The results showed that salinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 38 publications
6
23
0
Order By: Relevance
“…3). The increase in sugar concentrations in leaves is in line with the results reported for other species of the Lamiaceae such as Melissa officinalis ( Khalid and Cai , 2011), Ocimum basilicum ( Heidari , 2012), and Salvia miltiorrhiza ( Gengmao et al, 2014), in which the sugar concentration increased under salt stress. Soluble sugar fluctuations under salt stress can be due to changes in CO 2 assimilation, in source‐sink carbon partitioning and in activity of related enzymes ( Rosa et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…3). The increase in sugar concentrations in leaves is in line with the results reported for other species of the Lamiaceae such as Melissa officinalis ( Khalid and Cai , 2011), Ocimum basilicum ( Heidari , 2012), and Salvia miltiorrhiza ( Gengmao et al, 2014), in which the sugar concentration increased under salt stress. Soluble sugar fluctuations under salt stress can be due to changes in CO 2 assimilation, in source‐sink carbon partitioning and in activity of related enzymes ( Rosa et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…Application of salicylic acid ameliorated the effect of salinity, reduced the activity of APX and increased the activity of CAT in T. aestivum plants. This increase in CAT activity in response to salt stress in the present study was consistent with the results reported by Gengmao et al, [51]. It has been suggested that, the treated plants with SA concentration possess a better scavenging ability.…”
Section: Antioxidant Enzyme Activitysupporting
confidence: 93%
“…SA induced enhancement in the activity of CAT and APX in wheat plants contributed to quick neutralization of H2O2 and hence protecting the membranes from the toxic effects of stress. SA mediated increase in CAT activity under salt stress has also been reported by Gengmao et al, (2014). Interactive effect of salicylic acid and different levels of NaCl on activity of (A) SOD (B) CAT and (C) APX in wheat plants.…”
Section: Sa Application Improves the Synthesis Of Proline Free Aminomentioning
confidence: 52%